2021
DOI: 10.1590/1980-5373-mr-2021-0204
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Absorption/Desorption Behavior of a Cold-Rolled TiFe Intermetallic Compound

Abstract: The (de)hydrogenation properties of a TiFe intermetallic compound (IMC) alloy activated by cold rolling inside a glovebox at ambient temperature were investigated by kinetic measurements, x-ray powder diffraction (XRD), and transmission electron microscopy (TEM). Rate-limiting steps were identified by testing kinetic models on hydrogen absorption and desorption curves. To prevent surface poisoning during air exposure, the TiFe IMC was also cold rolled with polytetrafluoroethylene (PTFE) and ultra-high molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…The (110) surface forms with the lowest energy and has an area fraction of 57.2%, suggesting that it is the most preferred orientation for the TiFe IMC. This is in agreement with a previous theoretical study, 72 the (110) peak intensification observed in X-ray diffraction (XRD), 16,73,74 and the transmission electron microscopy (TEM) analysis of TiFe lattice planes. 16,73,75 Therefore, in the following we focused on the (110) orientation as the most representative surface of TiFe.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The (110) surface forms with the lowest energy and has an area fraction of 57.2%, suggesting that it is the most preferred orientation for the TiFe IMC. This is in agreement with a previous theoretical study, 72 the (110) peak intensification observed in X-ray diffraction (XRD), 16,73,74 and the transmission electron microscopy (TEM) analysis of TiFe lattice planes. 16,73,75 Therefore, in the following we focused on the (110) orientation as the most representative surface of TiFe.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with a previous theoretical study, 72 the (110) peak intensification observed in X-ray diffraction (XRD), 16,73,74 and the transmission electron microscopy (TEM) analysis of TiFe lattice planes. 16,73,75 Therefore, in the following we focused on the (110) orientation as the most representative surface of TiFe. As passivating oxide films are almost always present under actual operating conditions of the material, we discuss oxide layer formation, stability energetics and dynamics based on the TiFe (110) surface in the following subsections.…”
Section: Resultssupporting
confidence: 93%
“…Doping FeTi by Zr, Mn or Y additives promotes the activation of hydrogen uptake at room temperature, however, with a sluggish kinetics [40][41][42]. When FeTi alloy is subjected to SPD by different processing routes, such as HEBM, high-pressure torsion and groove or cold rolling, the formation of cracks and subgrain boundaries positively influence the activation of hydrogenation [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have pointed out that the Fe-Ti system is capable of absorbing and desorbing hydrogen [56,57]; however, the Fe-Ti alloys must be activated at relatively high temperatures (400-450 • C) [56]. Nevertheless, the activation of hydrogenation of Fe-Ti is positively influenced when the alloy is subjected to SPD by different processing routes, such as HEBM, high-pressure torsion and groove or cold rolling via the formation of cracks and subgrain boundaries [58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%